The prostatic utricle cyst with huge calculus and hypospadias: A case report and a review of the literature - Wang, Weigang; Wang, Yuantao; Zhu, Dezhun; Yan, Pengfei; Dong, Biao; Zhou, Honglan (Canadian Urological Association Journal, 2015)
Prostatic utricle cysts with calculus and hypospadias are rare in clinical practice. According to our literature review, only few cases have been reported. Recently, we experienced a case of prostatic utricle cyst with huge calculus in a 25-year-old male patient. He had a history of left cryptorchidism and surgery for penoscrotal hypospadias in his infancy. He was referred for frequent micturition, urgency of urination, urine pain, terminal hematuria and dysuria. Computed tomography (CT) revealed a retrovesical cystic lesion of low density, in which a 5×5 cm calcification was shown. Retrograde urethrocystography showed a 5×5 cm high-density shadow in the posterior urethra. The cyst was incised by transperineal approach and the stone was clearly observed and removed. Urethral stricture repair was performed simultaneously. The patient recovered smoothly after operation.